The role of psychological attribution in responses to weight stigma - Mary A. Gerend; Angelina R. Sutin; Antonio Terracciano; Jon K. Maner (Wiley, 2020)
Summary Objective Weight discrimination is associated with numerous negative health consequences. Little is known about early‐stage psychological mechanisms that explain variability in responses to weight discrimination among people with obesity. This study tested the hypothesis that attributing negative social evaluation to one's weight would be associated with stigma‐related stress responses (eg, reduced cognitive functioning and self‐esteem, increased negative affect and cortisol), especially among people who had experienced frequent weight discrimination in the past. Methods Adults (N = 109) with obesity were randomly assigned to receive a mildly positive (control) versus negative social evaluation. The extent to which participants attributed the negative evaluation to their physical appearance was assessed, along with negative affect, social and appearance self‐esteem, cognitive functioning and salivary cortisol. Results Participants who had experienced frequent weight discrimination in the past were more likely to attribute the negative evaluation to their appearance. Participants who attributed the negative evaluation to their appearance in turn experienced elevated negative affect, lower appearance self‐esteem and worse cognitive functioning. Conclusions This study is among the first to identify attribution as an early‐stage process underlying responses to weight stigma. Attribution may be a key psychological factor conferring risk for or protection from the negative effects of weight stigma.